SAR Reduction In The Human Head and Investigation of Impact of Radio Frequency Exposure on Children Health - Eslam M. Abo Dawwas; Wala Hanani; Manar Najjar (My University, 2015)
Abstract In the last few decades, our life is facing a continuous growth in different areas of technology especially in wireless communication which became an important part of human life. The most important aspect of this development is cellular network and its services such as communication and roaming for all users at home or abroad.The demand of using cell phones is increasing daily with the increasing offered services, this Leeds the operators to expand their networks and increase the number of cell phone towers on the roofs of buildings, and this in turn increases the people worry about their health which may affected by the spreading of communication towers.This project consists of  two phases, the first one is a SAR reduction as completion of previous work and the second is a study which focuses on the effect of electromagnetic radiation (EMR) emitted by cell phone towers and other types of towers such as T.V broadcast and radio stations on children  health, especially on arterial blood pressure (systolic (SBP), diastolic (DBP)), heart pulse rate (HR), body temperature (T) of children on kindergartens.In the first phase, a reduction of SAR value has been made after evaluating it in project one. The reduction has been made  by adding electromagnetic band gap (EBG) structure using CST software , The SAR over (1g) values using the EBG structures are reduced and are reduced in comparison with the PIFA value 44% in 0.9GHz and 69.2%  in 1.8GHz. In the second phase, the sample of  study is kids of both genders, distributed in two different kindergartens. The sample ages were between 5-6 years which randomly chosen to reach the desired objective. Many instruments  were used to complete the  wanted measurements which are Narda Broadband Field Meter NBM-550  for Measuring the EMR intensity, Electronic THM thermometer 392S to measure the Temperature   and Multi Function  Automatic blood pressure with children's cuff UA-851V/VL to measure Blood pressure and Heart pulse rate. The measured power intensity is bellow standard value, and the physical measurements have been measured before and after exposure.  Then, some calculations have been made to reach the final result of the study.

. .      .     ( (SBP ) (DBP)) (HR) (T)   . .   (EBG)   CST         EBG     44 EBG     0.9 GHz   69.2 1.8 GHz .      .   5-6 . Narda NBM-550 THM 392S  Multi _ Function      ,  .   .    24.25 / 2 45.24 / 2    0.4 0.21 3 15.49     0.9 5.48 3.5 3.76 .
SAR Reduction In The Human Head and Investigation of Impact of Radio Frequency Exposure on Children Health